PENGARUH TERAPI MUROTTAL AL-QUR’AN TERHADAP KECEMASAN IBU BERSALIN DI KECAMATAN SEPUTIH SURABAYA KABUPATEN LAMPUNG TENGAH TAHUN 2019 - Andi Julia Rifiana; Yarma Mita Sari (Jurnal Ilmu dan Budaya, 2020)
Anxiety causes physical or psychological impact on the mother's fetus and the delivery process that impacts on complications of labor. One of the nonpharmacological treatments is Murottal Al-Qur'an therapy. This study aims to determine the effect of Murottal Al-quran anxiety therapy on maternity in Seputih Surabaya, Central Lampung. This research is a pre-experimental research with one group pretest posttest design approach. The sample in this study which were 30 people. Data collection techniques using accidental sampling. The instrument of this study was a questionnaire about anxiety levels using the Hamilton Rating Scale for Anxiety (HRS-A). Data normality test uses kolmogrof-smirnov, bivariate analysis uses Paired t-test. The results of the study before the administration of Murottal Al-qu'an therapy had anxiety categories was 21-41 (severe) (73.3%) and after the administration of Murottal Al-qur'an therapy anxiety categories was <14 (mild) (66.7%). The normality test results obtained sig.2-tailed was 0.262 which more than 0.05. There is a significant effect of giving Murottal Al-Qur'an therapy to maternal anxiety.